Abamectin: efficiency against cotton aphid and effects on Cicloneda sanguinea and Pseudodoros clavatus - Ramalho, Francisco S.; Jesus, F. M. M. (Pesquisa Agropecuaria Brasileira, 2014)
This work was conducted under field conditions in the Zangalheira farm, at Gurinhém, PB, Brazil, in the cotton season, of 1985, using CNPA 2H cotton (Gossypium hirsutumL.) cultivar. The experimental design used in this study was in randomized complete-blocks with five treatments: (1) Abamectin (MK-936 1.8 EC), 5.0 g a.i/ha, (2) Abamectin (MK-936 1.8 EC), 7.5 g a.i/ha, (3) Abamectin (MK-936 1.8 EC), 10.0 g a.i/ha, (4) Demeton-S-methyl (Metasystox i 250 EC), 50.0 g a.i/ha, and (5) control (nothing was applied), in four replications. The results showed that the Abamectin (MK-936 1.8 EC), 5.0, 7.5 and 10.0 g a.i/ha and the Demeton-S-methyl (Metasystox i 250 EC), 50.0 g a.i/ha, were efficient against cotton aphid, Aphis gossypii, and selective to Cicloneda sanguinea and Pseudodoros clavatus, predators of this cotton aphid.